PERANAN WANITA NELAYAN (ISTRI NELAYAN) JARING INSANG DALAM MENINGKATKAN PENDAPATAN KELUARGA DI DESA BEJALEN, PERAIRAN RAWA PENING, KECAMATAN AMBARAWA, KABUPATEN SEMARANG - Hutapea, Roma; Kohar, Abdul; Rosyid, Abdul (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2012)
The role of fisher women is not only as a housewife but also the breadwinner, the fisher women have a dual role of women in her family. Fisher women help their husband working to fulfill family needs. The aims of the research are to discover contribution of gillnet fisher women’s income to family income and the factors that influence the gillnet fisher women’s income in Bejalen village. Descriptive method based on case study used in this research. The sampling method used in this research was purposive sampling, and total sample was 25 samples took from 60 fisher women samples. Data analysis used in this research were the Spearman Rank correlation test and multiple linear regression test. The results showed the women's role to improve the family income in Bejalen village by working in various business sectors with an average income of Rp634.000,00 per month with a contribution to family income by 37.11%. The highest fisher women’s income was Rp2.000.000,00 with 75,48% contribution to the family income and the lowest was Rp300.000,00 with 26% contribution to family income. The factors which influence the gillnet fisher women’s income significantly was working time. Fisherman’s income, age, member of family, and education were not influence significantly.